Improvement Strategy Sustainability in LMS- Based Islamic Religious Education Learning: An Approach, Measurement, Holistic, and Revision Systematic - Bidayatul Hubbil Iffah; Ummu Sa’diyah; Lilis Syifa’yah; Lailatul Fitria Fitria; Alaika M. Bagus Kurnia PS (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to examine strategies for enhancing the sustainability of Learning Management System (LMS)-based Islamic Religious Education (PAI) learning through the integration of holistic measurement and the Plan–Do–Check–Act (PDCA) cycle. PAI emphasizes holistic student development across cognitive, affective, and psychomotor domains grounded in Islamic spiritual values; however, LMS-based evaluation and revision practices remain fragmented and insufficiently systematic. This study employs a systematic literature review (SLR) following the PRISMA protocol, analyzing scholarly articles published between 2015 and 2024 from reputable databases such as Scopus and Google Scholar. Of the 150 articles initially identified, 45 met the inclusion criteria and were analyzed using qualitative thematic meta-synthesis. The findings reveal that LMS enhances learning flexibility and student engagement but remains limited in facilitating the internalization of Islamic values and sustainable revision mechanisms. This study proposes an original contribution in the form of a Holistic Adaptive PAI–PDCA Framework, integrating multidimensional assessment with adaptive feedback and continuous revision within LMS environments. Theoretically, this framework contributes to the development of Total Quality Management perspectives in Islamic education. Practically, it offers conceptual guidance for PAI teachers to optimize LMS implementation in a value-based and sustainable learning context. This study is limited by the absence of empirical validation; therefore, future longitudinal and mixed-method studies are recommended